Problemas recreativos na obra O Homem que Calculava, de Malba Tahan, e a resolução de problemas - Segantini, Clarice (2015)
This research aims at investigating and analysing the appropriations and representations of a particular group of high school students from “Nestor Gomes” Elementary and High School faced with problems from the book The Man who Counted, by Malba Tahan, in a problem-solving environment, as well as analysing the records kept by the students as they solved the problems. It presents a brief history of problem-solving, sometimes approached as content, others as practice, or yet seen as methodology. It shows important mathematicians as disseminators of recreational mathematics. It is a qualitative nature case study. It uses triangulation for data analysis. Roger Chartier's cultural history concepts of representation, appropriation and practice offers its theoretical framework. It describes students' output in the problem-solving workshops and indicates that recreational problems not only stimulate interest, creativity, imagination and the use of particular strategies for resolution but also encourage questioning, discussions and teamwork among students. It demonstrates students' difficulties with comprehension and mathematical calculations. It reports that the selected problems include cultural and social aspects, going beyond mathematical concepts.